2019
DOI: 10.3390/brainsci9100248
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electrophysiological Arguments in Favor of a Relationship between Impulsivity, Risk-Taking, and Success on the Iowa Gambling Task

Abstract: The aim of the present study was to investigate the relationship between trait impulsivity, risk-taking, and decision-making performance. We recruited 20 healthy participants who performed the Iowa Gambling Task (IGT) and the Balloon Analog Risk Task (BART) to measure decision-making and risk-taking. The impulsivity was measured by the Barratt Impulsiveness Scale. Resting-state neural activity was recorded to explore whether brain oscillatory rhythms provide important information about the dispositional trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…The term undecided was used to highlight that subjects from this group were unable to move toward a positive or negative strategy. These participants favored neither advantageous nor disadvantageous decks (Giustiniani et al, 2015(Giustiniani et al, , 2019. Table 1 shows the net scores for both groups.…”
Section: Group Assignmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The term undecided was used to highlight that subjects from this group were unable to move toward a positive or negative strategy. These participants favored neither advantageous nor disadvantageous decks (Giustiniani et al, 2015(Giustiniani et al, , 2019. Table 1 shows the net scores for both groups.…”
Section: Group Assignmentmentioning
confidence: 99%
“…From the 4th block on (i.e., 60th trial), participants' net score was significantly different from zero. Per previous studies, subjects were then classified, post hoc, into two groups differing in net score in blocks 4-10, favorable if the net score was higher than 10, unfavorable if the net score was less than -10 and undecided if the net score range was between 10 and -10 ( Bechara et al, 1994Bechara et al, , 2000aBechara and Damasio, 2002;Giustiniani et al, 2015Giustiniani et al, , 2019. In the pool of 32 participants, fourteen subjects were found to develop a correct strategy and were assigned to the favorable group (mean age: 25.4 ±/ 5.9).…”
Section: Group Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the GDT is an exclusive decision-making task under risk, without learning by feedback. These tests have been used in numerous studies in both healthy young and older populations, as well as in clinical populations (with psychiatric disorders, in particular) [16][17][18]. These studies have shown qualitative and quantitative differences in behavioral strategies in these tasks as a function of age, the presence of neurological lesions and/or neuropsychiatric pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the explanation of PFC unilateralization did not take into account the psychological activities involved, nor did it take into account the differences between actions in preparation and execution. Moreover, Giustiniani et al (2019) research found that the unilateralization of the resting alpha level of PFC was only related to risky behavior, and not directly related to IGT performance. Therefore, whether the resting alpha level can be used as an indicator of somatic signals still needs further investigation.…”
Section: Event-related Potentialmentioning
confidence: 96%